Penyelesaian Sengketa Nusyuz dan Syiqaq dalam Perspektif Al-Qur’an - Hidayat, Taufik; Sayehu; Usman (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
Islam protects the marriage bond with various guarantees, while making it a sacred act. Every marriage aims to form a harmonious family. However, in life there are bound to be problems. Likewise, when running a household, there are times when disputes occur between husband and wife. The cause of disputes that arise in the household is a form of disobedience to obligations carried out between husband or wife, this form in Islam is called an act of nusyuz. Meanwhile, shiqaq arises when the husband or wife or both do not carry out the obligations they must carry out. When there is a family conflict. In this research, the author uses a method of interpreting the Al-Qur'an which discusses a particular theme, either in the form of surahs or special topics by collecting and analyzing the content of verses related to the theme. The conclusion in answer to the problem formulation above is that the act of nusyuz is an act that is prohibited by religion, because this is a factor that triggers the collapse of a household, so husbands and wives are required to be able to resolve the problems in their household, including problems regarding nusyuz in order to maintain family welfare. Keywords: nusyuz, syiqaq, family, tafsir al-Qur'an